2015
DOI: 10.1186/s12879-015-1090-x
|View full text |Cite
|
Sign up to set email alerts
|

Sustained low influenza vaccination in health care workers after H1N1 pandemic: a cross sectional study in an Italian health care setting for at-risk patients

Abstract: BackgroundDespite consistent recommendations by all Public Health Authorities in support of annual influenza vaccination for at-risk categories, there is still a low uptake of influenza vaccine in these groups including health care workers (HCWs). Aim of this observational two-phase study was to estimate the immunization rates for influenza in four subsequent seasons and for pandemic H1N1 influenza in HCWs of a University Hospital, and to investigate its distribution pattern and the main determinants of immuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 23 publications
(26 reference statements)
4
27
0
2
Order By: Relevance
“…Since risk perception of vaccination rates is higher in pandemics periods, Sevencan et al found the rates 36.4% whereas Ormen et al detected the rates up to 40.0% [13,14]. The reason for lower rates of vaccination in similar studies conducted worldwide is similar to the reasons detected in our country [15,16,17]. The most common reasons for rejection of the vaccination include being afraid of side effects of the vaccine, not believing the effectiveness of the vaccine and not considering the vaccine safe [18].…”
Section: Discussionsupporting
confidence: 76%
“…Since risk perception of vaccination rates is higher in pandemics periods, Sevencan et al found the rates 36.4% whereas Ormen et al detected the rates up to 40.0% [13,14]. The reason for lower rates of vaccination in similar studies conducted worldwide is similar to the reasons detected in our country [15,16,17]. The most common reasons for rejection of the vaccination include being afraid of side effects of the vaccine, not believing the effectiveness of the vaccine and not considering the vaccine safe [18].…”
Section: Discussionsupporting
confidence: 76%
“…Our data are consistent with findings from several other studies in that vaccine uptake is significantly lower for nurses than physicians. 18,[27][28][29][30][31][32][33] One study determined that physicians had a higher level of knowledge about influenza and influenza vaccines were less likely to expect a severe reaction to the vaccine, and more likely to consider influenza vaccines effective than nurses. 18 Similarly, increased knowledge levels and beliefs that influenza is a serious illness and that vaccinations are safe were associated with higher uptake among nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Several reasons for receiving and not receiving vaccination have been identified in the literatures. For example, studies have shown that the common reasons for not receiving vaccination among nurses included low levels of risk perception, concerns about side effects, questions about vaccine's effectiveness/safety, inconvenience in accessing vaccination, fear of pain, or negative reports from media (Ajenjo et al, 2010;Clark, Cowan, & Wortley, 2009;Corace et al, 2013;Giannattasio et al, 2015;Hollmeyer, Hayden, Poland, & Buchholz, 2009;Maltezou et al, 2008;Schmid, Rauber, Betsch, Lidolt, & Denker, 2017;Wang, Lee, & Lee, 2015;Weingarten, Riedinger, Bolton, Miles, & Ault, 1989;Zhang, While, & Norman, 2011). On the other hand, the reasons for receiving vaccination among nurses included protecting oneself, patient, family members, friends and children, to avoid sick leave, recommendation/mandate by employer, perception of vaccine's effectiveness/ safety and accessibility of vaccination (Haviari et al, 2015;Hollmeyer et al, 2009;Maltezou et al, 2008;Tosh, Jacobson, & Poland, 2010;Zhang et al, 2011).…”
Section: Determinants Of Getting Influenza Vaccinationmentioning
confidence: 99%